The Assessment of the Integrated Antioxidant System of the Body in the Course of Radon Therapy: A Pilot Study. (2nd January 2018) - Kuciel-Lewandowska, Jadwiga; Gnus, Jan; Pawlik-Sobecka, Lilla; Płaczkowska, Sylwia; Kokot, Izabela; Kasperczak, Michał; Paprocka-Borowicz, Małgorzata
Abstract : Introduction . The sources of Reactive Oxidative Species (ROS) in the organism are the respiratory processes occurring in cells catalyzed by different enzymes. Operation of ROS is balanced by antioxidants, the compounds; although present in low concentrations, they significantly inhibit the degree of oxidation of particular molecules. The Aim of the Study . The aim of this study was to assess the changes in the integrated antioxidant system under the influence of radon therapy in osteoarthritis patients. Material and Methods . Observation included 35 patients suffering from degenerative joints and disc disease (mean age 56.5 years) undergoing radon water therapy and control group that consisted of 15 osteoarthritis patients (mean age 54.2) without contact with radon water. Before therapy and after 18 days of treatment, serum total antioxidant status (TAS) was assessed with the use of standard colorimetric assay. Results . In the study group, we observed trends to increase TAS concentration, whereas, in the control group, TAS concentration was decreasing. Conclusions . (1) Radon waters treatment influenced the level of TAS of osteoarthritis patients treated with the radon water. (2) The change in TAS concentrations in the study group may be the result of low doses of ionizing radiation, but further studies on larger patient's groups are demanded. This study is registered with numberNCT03274128 .